Multiple giant eruptions and X-ray emission in the recoiling AGN/LBV candidate SDSS1133. Issue 1 (17th June 2022) - Kokubo, Mitsuru
ABSTRACT: We present a comprehensive analysis of 20 yr worth of multicolour photometric light curves, multiepoch optical spectra, and X-ray data of an off-nuclear variable object SDSS1133 in Mrk 177 at z = 0.0079. The UV-optical light curves reveal that SDSS1133 experienced four outbursts in 2001, 2014, 2019, and 2021. The persistent UV-optical luminosity in the non-outbursting state is ∼10 41 erg s −1 with small-scale flux variations, and peak luminosities during the outbursts reach ∼10 42 erg s −1 . The optical spectra exhibit enduring broad hydrogen Balmer P-Cygni profiles with the absorption minimum at ∼−2000 km s −1, indicating the presence of fast-moving ejecta. Chandra detected weak X-ray emission at a 0.3−10-keV luminosity of LX = 4 × 10 38 erg s −1 after the 2019 outburst. These lines of evidence suggests that SDSS1133 is an extreme luminous blue variable (LBV) star experiencing multiple giant eruptions with interactions of the ejected shell with different shells and/or circumstellar medium (CSM), and disfavours the recoiling active galactic nuclei scenario suggested in the literature. We suggest that pulsational pair-instability may provide a viable explanation for the multiple energetic eruptions in SDSS1133. If the current activity of SDSS1133 is a precursor of a supernova explosion, we may be able to observe a few additional giant eruptions and then the terminal supernova explosion or collapse to a massive black hole in future observations.